1991
DOI: 10.1007/bf00308813
|View full text |Cite
|
Sign up to set email alerts
|

Re-examination of ex-boxers' brains using immunohistochemistry with antibodies to amyloid ?-protein and tau protein

Abstract: A histopathological study was carried out on the brains of eight ex-boxers (ages 56 to 83) using conventional histological staining methods and immunocytochemistry with antibodies to amyloid beta-protein and the PHF-related tau protein. All cases showed a large number of tau-immunoreactive neurofibrillary tangles and also beta-protein immunoreactive senile plaques in the cortex. In the areas with many neurofibrillary tangles, neuropil threads with tau-immunoreactivity were also observed, and some of the senile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(121 citation statements)
references
References 41 publications
5
114
2
Order By: Relevance
“…At autopsy, these athletes had pathologic changes to the brain, including ventriculomegaly, cerebral atrophy, b-amyloid deposits, and phosphorylated t deposits, an entity now commonly known as CTE. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] These case reports and case series have led to the hypothesis that repetitive blows to the head, whether concussive or subconcussive, result in the pathologic changes noted above and that these pathologic changes are associated with certain neurobehavioral characteristics. Whether the pathologic findings are solely attributable to the blows to the head and whether the pathologic changes are significantly associated with the neurobehavioral correlates is debated because these hypotheses remain to be tested by case-control and cohort studies.…”
Section: Cumulative and Catastrophic Head And Neck Injuries In Footballmentioning
confidence: 99%
“…At autopsy, these athletes had pathologic changes to the brain, including ventriculomegaly, cerebral atrophy, b-amyloid deposits, and phosphorylated t deposits, an entity now commonly known as CTE. [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] These case reports and case series have led to the hypothesis that repetitive blows to the head, whether concussive or subconcussive, result in the pathologic changes noted above and that these pathologic changes are associated with certain neurobehavioral characteristics. Whether the pathologic findings are solely attributable to the blows to the head and whether the pathologic changes are significantly associated with the neurobehavioral correlates is debated because these hypotheses remain to be tested by case-control and cohort studies.…”
Section: Cumulative and Catastrophic Head And Neck Injuries In Footballmentioning
confidence: 99%
“…AD-including deposition of plaques containing ␤-amyloid (A␤) derived from the proteolysis of amyloid precursor protein (APP) and composed of fibrils formed by 39-43 amino acid peptides, and the presence of neurofibrillary tangles in which paired helical filaments are composed of abnormally phosphorylated tau (Tokuda et al, 1991;Roberts et al, 1994). Alzheimer disease is believed to be profoundly influenced by genotype.…”
Section: Longhi Et Al 1250mentioning
confidence: 99%
“…Particularly interesting will be the study of the novel molecules ABri and ADan, originated from different defects in a gene not previously known to be related to human neurological disorders. Immunohistochemical and electron microscopical studies have demonstrated that the cytoskeletal pathology in FBD and FDD patients is identical to that seen in patients with other neurodegenerative conditions, including Alzheimer disease, Prion disorders, brain trauma, or mutations in chromosome 17 [4,7,14,42,53]. Therefore, different amyloid peptides at distinct cerebral areas could trigger similar neuropathological changes leading to the same scenario: neuronal loss and dementia, supporting the notion that amyloid peptides may be of primary importance in the initiation of neurodegeneration.…”
Section: Resultsmentioning
confidence: 78%